Kedudukan Saksi Yang Mempunyai Hubungan Darah Dalam Perkara Tindak Pidana Penculikan Anak/Bayi - Jati, Leonardo (Sebelas Maret University, 2017)
Research discussed do self defense the defendant by asking sister of as a witness a de charge in of crimes kidnapping children/of infants have in accordance with the article 65 jo verse 168 KUHAP, second do filing witness a de charge considered the judge in dropped decisions criminal against the defendant the kidnapping children/of infants have in accordance with the article 183 jo verse 193 paragraph (1) KUHAP. The defendant seek for information about posedur adoption kid to the hospital dr. soeselo slawi, but the defendant having an intention to take of infants that did not in fail by their parents. After the baby be in his hand they go home with a view it their own. The kind of research using research normative that is prespektif and applied, and used the cases.The results of the study: (1)is in accordance with article 65 KUHAP the defendant has the right to lodge witness a de a charge; but not in accordance with article 168 KUHAP the sister of not allowed witness. (2)filing witness a de charge in considerataion of the judges are not considered as sisterof must not be a witness,,while consideration the judges in droped the award hasin accordance with article 183 jo verse 193 paragraph (1) KUHAP, Having been paying at least two evidence legitimate and court thought the defendant guilty criminal charged him Keywords: witness a de a charge; kidnapping children / baby